Physical exercise in motivating and stimulating environment - Medini, Ksenija; Petrović, Vanja; Alić, Jelena (Rethinking childhood II: child and space, 2026)
In institutions concerning early and preschool upbringing and education, physical education of children of early and preschool age occupies a special place. Using different physical activities, children get to know natural forms of movement, general preparatory physical exercises, find their way independently in their environment and learn ontogenetic motor skills that they will apply in future physical activities. In addition to the development of kinanthropological features, physical activities also influence the proper psychological development of the child, which includes the formation of aesthetic feelings, moral and volitional qualities of each child; i.e., “children need to move in order to develop healthily and feel good, because movement is the basis for brain development” (Baureis, Wagenmann, 2015:73). For children, the movement that is carried out using different forms of games is a biological need; i.e., “through play, children get to know the world: they explore connections and relationships, explore the environment, enter into relationships and set boundaries. Through play, mental, motor, emotional and social skills are exercised and strengthened” (Baureis, Wagenmann, 2015:124). Games allow children to perceive the environment they are in and encourage the development of all senses. Games as such are interesting for children and have positive effects on their psychophysical development. By actively involving adults in playing with the child, they are enabled to directly participate in the child’s development and encourage it. When choosing a physical activity, children’s interests should be taken into account so that they are motivated to participate and actively participate. Children should be in a stimulating environment in order to be physically active as much as possible, for example: adults can encourage children to exercise by going to nature, hiking, going to the park, on a trip, etc., or simply create a materially stimulating environment. By creating a stimulating spatial environment, the child is encouraged to move on his own initiative, which of course contributes to more proper motor development. In educational institutions for early and preschool education, stimulating exercises can be integrated into everyday educational work. It is important and necessary to harmonise the content of stimulating exercises with the age of the child as well as material conditions. We encourage children to decide on their own initiative how they would move: crawling, dancing, jumping and similar. Exercise can be done indoors in the living room, and in open spaces such as the terrace, park, children’s playground and sports field. Corridors in educational institutions can become centres of physical exercise. Physical exercise should arouse positive emotions in the child, exclude stressful situations and provide them with sufficient intensity and a wide range of motor actions, and finally—allow them an individual and differentiated approach in choosing exercises. It is also very important to take care of rest, activity schedule, children’s health, climate and weather conditions, children’s clothes and shoes. The acquisition of healthy habits should be conveyed to children in a fun way, raising awareness for the rest of their lives. Parents, educators and the community should cooperate and participate in the development of children’s health habits. Regular exercise is an indicator of a quality and active lifestyle. In addition to the fact that physical exercise has a great impact on the health of every child, it is also important for socialisation and generally has an enriching and ennobling effect on the child’s life. The habits that children adopt in preschool age are reflected in their overall development and are most often retained in later periods of life.